Development of Video Tutorial Based Learning Media for Underhand Pass Basic Techniques in Volleyball in 7th Grades at SMPN 2 Singaraja - I Kadek Dyas Saputra; I Made Satyawan; I Komang Sukarata Adnyana (Universitas Pendidikan Ganesha, 2024)
The subject of volleyball is widely taught at the educational level using various types of media. The aim of this research is to develop learning media based on video tutorials about basic passing techniques in class VII volleyball at SMP Negeri 2 Singaraja. The type of research used is the development type with the ADDIE development model which has five stages of analysis, design, development, implementation, evaluation. The development product has been validated by content experts, design experts and learning media experts as well as field practitioner experts. Sample trials for this product are individual trials with 3 students, small group trials with 6 students, field trials with one class with 30 students. This research uses assessment instruments and descriptive-qualitative and descriptive-quantitative analysis techniques. By obtaining product validation results, the learning content expert test was found to be 93% in the very good category, the design and learning media expert test was 97% in the very good category, and the field practitioner expert test was 95% in the very good category. For individual trials 96% were in the very good category, for small group trials 96% were in the very good category, for large group trials 94% were in the very good category. So it can be concluded that video-based learning media, tutorials on basic passing techniques in class VII volleyball, are very suitable to be used as learning resources and media so that they can improve student learning outcomes.